Atrase B, a novel metalloprotease with anti‐complement and anti‐coagulant activity, significantly delays discordant cardiac xenograft rejection. (12th June 2020) - Fu, Cheng; Shi, Lei; Huang, Xia; Feng, Hao; Tan, Xiaosheng; Chen, Song; Zhu, Lan; Sun, Qianyun; Chen, Gang
Abstract: Background: Both the complement and the coagulation systems play important roles in the development of hyperacute or acute antibody‐mediated xenograft rejection. Atrase B is a novel metalloproteinase isolated from the venom of Naja atra . In this study, we investigated the inhibitory effects of atrase B on complement activation and coagulation, as well as the effect on xenograft survival in a discordant xenotransplantation model. Methods: The in vitro anti‐complement activity of atrase B was evaluated using a normal human serum (NHS)‐mediated complement‐dependent cytotoxicity model with an immortalized porcine aortic endothelial cell line (iPEC) as the target. The in vivo inhibitory effects on complement activity and coagulation function were measured in rats after the administration of atrase B. Guinea pig hearts were transplanted heterotopically into Wistar rats with or without atrase B pre‐treatment. Results: Pre‐treatment of the NHS with atrase B inhibited the cell lysis of iPECs in a dose‐dependent manner. FACS analysis showed that atrase B potently suppressed the deposition of C5b‐9, but not C3c and C4c, on iPECs. In vivo, atrase B‐treated rats showed a significant reduction in serum complement activity; markedly prolonged PT, APTT, and TT; and a decreased plasma level of fibrinogen. When compared to PBS treatment evaluated at study endpoint, atrase B treatment significantly delayed xenograft rejection and attenuated pathologic damage, the formation of platelet microthrombi, and the deposition of fibrin and C5b‐9. Conclusions: The dual activities of anti‐complement and anti‐coagulation make atrase B a potential adjuvant therapeutic drug for use in xenotransplantation.